Continuous Theta-Burst Stimulation Promotes Paravascular CSF-Interstitial Fluid Exchange through Regulation of Aquaporin-4 Polarization in APP/PS1 Mice. (19th August 2022) - Wu, Cheng; Lin, Tuo; Ding, Qian; Zhang, Ni; Ou, Zi-tong; Cai, Gui-yuan; Chen, Hong-ying; Xu, Jia-yue; Li, Ge; Pei, Zhong; Xu, Guang-qing; Lan, Yue
Abstract : Amyloid- β (A β ) deposition plays a crucial role in the occurrence and development of Alzheimer's disease (AD), and impaired A β clearance is the leading cause of A β deposition. Recently, studies have found that the glymphatic system performs similar functions to the peripheral lymphatic system. Glymphatic fluid transport mainly consists of cerebrospinal fluid (CSF) entering the brain from the paravascular space (PVS) by penetrating arteries and CSF and interstitial fluid exchanging mediated by aquaporin-4 (AQP4). This system promotes the drainage of interstitial fluid (ISF) in the parenchyma and removes metabolic waste, including A β, in the brain. Glymphatic system dysfunction plays an essential role in the occurrence and progression of AD. Regulation of glymphatic fluid transport may be a critical target for AD therapy. This study explored the regulatory effects of continuous theta-burst stimulation (CTBS) on the glymphatic system in APPswe/PS1dE9 (APP/PS1) mice with two-photon imaging. The results demonstrated that CTBS could increase glymphatic fluid transport, especially CSF and ISF exchange, mediated by improved AQP4 polarization. In addition, the accelerated glymphatic pathway reduced A β deposition and enhanced spatial memory cognition. It provided new insight into the clinical prevention and treatment of A β deposition-related diseases.